Enhancing Students’ Writing Skill Through the Use of Peer-Editing Technique : (A Classroom Action Research to the 11th Grade Students of Smk Negeri 1 Teluk Keramat) - Ayuda, Sri; Yohanes Gatot Sutapa Yuliana; Yanti Sri Rezeki; Rahayu Apriliaswati; Surmiyati (Kirana Publisher (KNPub), 2023)
This study aims to solve the problems found in students’ writing especially the errors in the use of authorial and secretarial aspects to the 11th grade students from OTKP major SMK Negeri 1 Teluk Keramat in the academic year 2021/2022. Using Classroom Action Research (CAR), this study tried to improve students’ writing skill of personal letter by the use of the peer-editing technique. The participants of this research were the 11th grade students of Otomatisasi dan Tata Kelola Perkantoran (OTKP) major. The data were collected through observation and documentation. The data were analyst using quantitative and thematic analysist technique. The results showed that the use of the peer-editing technique successfully improved students’ writings skill of personal letter. It was found through the process of using the peer-editing technique, students were likely to give various types of comments and suggestions in the text structure, grammar, vocabulary, punctuation, and spelling. The improvement of students’ writing results occurred in both authorial (text structure, grammar, vocabulary) and secretarial (punctuation, spelling) aspects. Therefore, this classroom action research was successful. Students’ writing skill was improved gradually by the use of the peer-editing technique.